'And Introducing Elvis Presley': Industrial Convergence and Transmedia Stardom in the Rock 'n' Roll Movie. Issue 2 (December 2015) - Palmer, Landon
Abstract : Recent cinema music scholarship has demonstrated that the correspondence between commercial music production and Hollywood filmmaking has rarely operated according to a stable or fixed formula, but has instead taken place as an ever-shifting negotiation between media industries. Through a case study that examines the production histories and promotional efforts of Elvis Presley's first two films, this essay builds upon existing scholarship to propose a political economy of film music stardom as a means to historicise the intersections between media industries. By applying the methodologies and concepts of comparative media studies to a history of postwar Hollywood that found itself challenged by a proliferation of 'new' media, particularly in the emergence of a youth-oriented consumer culture and the increasingly popular competing screen of television, this article demonstrates how transmedia stardom indexes the ways in which production cultures have understood the development of media industries and commodities in relation to one another.